The Small Entrepreneur in Fragile and Conflict-Affected Situations - Speakman, John; Rysova, Annoula (World Bank, Washington, DC, 2014)
This report is part of a broader effort by the World Bank Group to understand the motives and challenges of small entrepreneurs in fragile and conflict-affected situations (FCS). The report's key finding is that, compared to entrepreneurs elsewhere, entrepreneurs in FCS have different characteristics, face significantly different challenges, and thus may be subject to different incentives and have different motives. Therefore, it is recommended that both the current analytical approach and the operational strategy of the World Bank be informed by the findings that follow. The publication is organized in the following manner: (i) Overview of the Entrepreneur's Challenges in FCS; (ii) Observations of FCS Firms, Sectors, and Business Environments; (iii) Implications of findings; and (iv) Conclusions and Recommendations. Included are also appendices, boxes, figures, and tables.